Answer:
Proved
Step-by-step explanation:
Required
Prove that:
[tex](x\ sin\ a + y\ cos\ a)^2 + (x\ cos\ a - y\ sin\ a)^2 = x^2 + y^2[/tex]
Solving from left to right:
Open brackets
[tex](x\ sin\ a + y\ cos\ a)(x\ sin\ a + y\ cos\ a) + (x\ cos\ a - y\ sin\ a)(x\ cos\ a - y\ sin\ a) = x^2 + y^2[/tex][tex]x^2\ sin^2 a + 2xy\ sin\ a\ cos\ a + y^2\ cos^2 a + x^2\ cos^2 a - 2xy\ sin\ a\ cos\ a + y^2\ sin^2 a = x^2 + y^2[/tex]
Collect Like Terms
[tex]x^2\ sin^2 a + 2xy\ sin\ a\ cos\ a - 2xy\ sin\ a\ cos\ a + y^2\ cos^2 a + x^2\ cos^2 a+ y^2\ sin^2 a = x^2 + y^2[/tex]
[tex]x^2\ sin^2 a + y^2\ cos^2 a + x^2\ cos^2 a+ y^2\ sin^2 a = x^2 + y^2[/tex]
Collect Like Terms
[tex]x^2\ sin^2 a + y^2\ sin^2 a + x^2\ cos^2 a + y^2\ cos^2 a = x^2 + y^2[/tex]
Factorize:
[tex](x^2 + y^2)\ sin^2 a + (x^2 + y^2) cos^2 a = x^2 + y^2[/tex]
Further factorize
[tex](x^2 + y^2)(sin^2 a + cos^2 a) = x^2 + y^2[/tex]
In trigonometry:
[tex]sin^2 a + cos^2 a = 1[/tex]
So, we have:
[tex](x^2 + y^2)(1) = x^2 + y^2[/tex]
[tex]x^2 + y^2 = x^2 + y^2[/tex]
Proved